Conceitos axiológicos em atividades de leitura no livro didático da EJA - Vieira, Flávia Gumieiro (2022)
In this study, based on the assumptions of the dialogism of the Bakhtin Circle, we sought to understand how social axiologies are manifested in the reading proposals in the Youth abd Adult Education (EJA) textbook. For this purpose, the reading activities related to the genres strip, cartoon and chronicle, from the book “Walk and Transform: Portuguese Language, Final Years of Elementary School” (FERREIRA, 2013) are taken as corpus. From a qualitative documentary perspective, we analyse which and how social values permeate the reading proposals presented in the book. In a complementary way, extensions to the activities suggested in the textbook are presented in order to instigate in the EJA student the counter-words and a critical positioning in the face of discourses and social reality, which characterizes the research as prospective. The results indicated that: a) no all the reading activities in the textbook contemplate social values, but the texts allow the axiologies to be explored; b) the questions in which social values are present help in the formation of the critical and responsive reader; c) with the expansion of reading activities, students can take a valuable position before the text, society and the world, producing meanings to the texts.